A Convenient Process for the Preparation of Heteroaryl Trifluoromethyl Selenoethers. Issue 5 (25th April 2016) - Tian, Qinli; Weng, Zhiqiang
Abstract: The preparation of heteroaryl trifluoromethyl selenoethers by the trifluoromethylselenolation of heteroaryl bromides with [(bpy)CuSeCF3 ]2 was investigated. Using this approach, a large number of trifluoromethylselenolated heterocyclic compounds were synthesized in good to excellent yields. It was demonstrated that this procedure tolerates a wide variety of functional groups. Abstract : The synthesis of heteroaryl trifluoromethyl selenoethers by the trifluoromethylselenolation of heteroaryl bromides with [(bpy)CuSeCF3 ]2 was investigated. The reaction affords a variety of trifluoromethylselenolated heterocyclic compounds in good yields and tolerates a range of functional groups.